Inefficient CAR-proximal signaling blunts antigen sensitivity - Gudipati, Venugopal; Rydzek, Julian; Doel-Perez, Iago; Goncalves, Vasco Dos Reis; Scharf, Lydia; Koenigsberger, Sebastian; Lobner, Elisabeth; Kunert, Renate; Einsele, Hermann; Stockinger, Hannes; Hudecek, Michael; Huppa, Johannes B. (Nature Immunology, 2020)
Rational design of chimeric antigen receptors (CARs) with optimized anticancer performance mandates detailed knowledge of how CARs engage tumor antigens and how antigen engagement triggers activation. We analyzed CAR-mediated antigen recognition via quantitative, single-molecule, live-cell imaging and found the sensitivity of CAR T cells toward antigen approximately 1,000-times reduced as compared to T cell antigen-receptor-mediated recognition of nominal peptide–major histocompatibility complexes. While CARs outperformed T cell antigen receptors with regard to antigen binding within the immunological synapse, proximal signaling was significantly attenuated due to inefficient recruitment of the tyrosine-protein kinase ZAP-70 to ligated CARs and its reduced concomitant activation and subsequent release. Our study exposes signaling deficiencies of state-of-the-art CAR designs, which presently limit the efficacy of CAR T cell therapies to target tumors with diminished antigen expression.
CRIS-Team Scopus Importer:2023-03-23